(untitled) (Vietnam Journal of Community Medicine, 2026)
Objectives: (1) Describe and stratify early postoperative complications by Clavien-Dindo grade, distinguishing subclinical from symptomatic lymphocele; (2) Evaluate lower limb lymphedema at 3 months and 12 months postoperatively; (3) Analyze the association between lymphedema and pN status. Methods: A prospective descriptive case series of 38 penile cancer patients who underwent bilateral VEIL at Binh Dan Hospital (from May 2023 to June 2025). Complications were classified by Clavien-Dindo; lymphocele was stratified into subclinical (ultrasound-detected, asymptomatic) and symptomatic (requiring medical intervention). Lymphedema was assessed at 3 months and 12 months postoperatively; association with pN analyzed by Fisher’s exact test. Results: All 38 bilateral VEIL procedures were completed successfully (100%). Mean total operative time was 158.1 ± 25.6 min; estimated blood loss was 82.5 ± 34.1 mL. Great saphenous vein was preserved in 100% per side. Total lymphocele detection by systematic ultrasonography was 92.1% (35/38 patients); of these, 71.1% (27/38 patients) were subclinical and 21.1% (8/38 patients) were symptomatic. Wound infection: 5.2%; no skin necrosis or deep vein thrombosis (0%). Clavien-Dindo: grade 0: 7.9%; grade I: 71.1%; grade II: 18.4%; grade IIIa: 2.6%. Patient-reported lower-limb lymphedema was identified in 10.5% at 12 months based on clinical assessment; the rate was significantly higher in pN-positive versus pN0 patients (37.5% vs. 3.3%, p = 0.035). Conclusion: VEIL demonstrated low major complication rates (grade ≥ III: 2.6%), no skin necrosis or deep vein thrombosis. The symptomatic lymphocele rate (21.1%) aligns with recent meta-analyses (15-40%). Lymphedema was acceptable (10.5%) due to successful saphenous vein preservation and was significantly associated with pN-positive status.